Comparison of the Effectiveness of Group-Based Acceptance and Commitment Therapy and Compassion-Focused Therapy on Psychological Capital in Infertile Women - Yadolahi , Sara; Mirzaei, Seyed Hassan; Soleimanian , Ali Akbar (Psychology of Woman Journal, 2025)
Objective: The present study aimed to compare the effects of group counseling based on Acceptance and Commitment Therapy (ACT) and Compassion-Focused Therapy (CFT) on the psychological capital of infertile women. Methods and Materials: This research was a quasi-experimental study with a pretest-posttest design and a control group. The study population included all infertile women in Bojnord in 2023. A total of 45 participants were selected using purposive sampling and randomly assigned to three groups of 15 individuals (two experimental groups and one control group). The experimental interventions—one based on ACT and the other on CFT—were conducted in eight sessions lasting 120 minutes each for the experimental groups. The research instrument was the Psychological Capital Questionnaire developed by Luthans (2007). Findings: The findings indicated that the effects of time, group, and the interaction between time and group were all statistically significant (p < .001). Pairwise comparisons revealed no significant difference between the two therapeutic approaches (ACT and CFT) in the posttest. However, both experimental groups showed statistically significant improvements compared to the control group in all dimensions of psychological capital—hope, self-efficacy, optimism, and resilience (p < .01). Conclusion: The results suggest that group counseling based on ACT and CFT can be used to improve the psychological capital of infertile women, thereby potentially reducing the psychological and familial consequences of infertility, as well as the risk of increased conflict and divorce.